Discerning the thermal cyclotrimerizations of fluoro- and chloroacetylenes through ELF, NBO descriptors and QTAIM analysis: pseudodiradical character. Issue 7 (July 2020) - Morales-Bayuelo, Alejandro; Sánchez-Márquez, Jesús
Abstract: In this study the thermal cyclotrimerization reactions of fluoro- and chloroacetylenes involving regioselectively stepwise {2 + 2} and stepwise {4 + 2} cycloadditions were studied using the topological analysis of the electron localization function (ELF), the quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO) analyses. These methodologies have shown that the electronic reorganization in the regioselectively stepwise {2 + 2} and stepwise {4 + 2} cycloadditions may be considered as {2n+2n} and {2π+2n} pseudodiradical process, respectively. Finally, the last phase of this thermal reaction can be understood as an electronic migration process under the pseudodiradical character in the thermal ring-opening reaction, with the subsequent formation of reaction products. In this sense, new insights are reported on the electronic behavior in the bond formation in the thermal cyclotrimerization of fluoroacetylene. Abstract : Materials chemistry, Theoretical chemistry, Cyclotrimerization reactions: fluoro- and chloroacetylenes, Electron localization function (ELF), QTAIM, NBO analysis, {2 + 2}, {4 + 2} cycloadditions, {2n+2n} and {2π+2n} pseudodiradical process, Density functional theory (DFT).